The Rejected Stone May Be the Cornerstone : A Case for the Retention of Traditional Justice Systems as the Best Fora for Community Land Disputes in Kenya (Strathmore Law Review, 2016)
The resolution of community land disputes is not catered for adequately in Kenyan policy, law and practice. The Traditional Justice Systems (hereinafter TJS) initially used by communities were phased out with the introduction of laws based on western models of ownership. They were and are still viewed as retrogressive and backward. However, the formal systems introduced do not afford access to justice for all due to the complex procedures and high costs. This is the case even while TJS remain the most appropriate forum for resolving community land disputes. Their informal and community inclusive nature as well as resolution of disputes in the pursuit of restorative justice provide the best forum for resolution of community land disputes. This is owing to the fact that community land ownership is characterized by a web of interests and relationships where land rights are held by different individuals and groups with diverse interests. These relationships, therefore, need to be preserved for the communities to live harmoniously. TJS practices in Ghana and South Sudan are briefly examined in seeking to establish these aspects.